A Validated RP-HPLC Method for the Determination of Citrinin in Xuezhikang Capsule and other Monascus-Fermented Products. Issue 1 (2012) - Xue-Mei, Li; Xing-Hai, Shen; Lan, Xue; Zhen-Wen, Duan; Shu-Ren, Guo
Abstract : Citrinin is a toxic product usually produced during the Monascus fermentation. The presence of citrinin in xuezhikang capsule has been a concern due to its ingredient which is derived from monascus -fermented rice. A rapid and sensitive RP-HPLC method with fluorescence detection at λex = 331 nm and λem = 500 nm for analysis of citrinin in Monascus -fermented products was developed to analyze citrinin in Monascus -fermented products. The chromatography was performed with mobile phase containing acidified water and acetonitrile. The calibration curve was linear (r = 0.9999) over a range of 0.0107- 0.537 μg/mL. The limit of detection (LOD) and the limit of quantitation (LOQ) were 0.187 ng/mL and 0.6 ng/mL respectively. The analysis of xuezhikang capsules using the developed method suggested that the product does not contain detectable citrinin and the result has been further confirmed using independent LC-MS/MS analysis. The proposed method has also been applied to analyze 11 samples of other Monascus -fermented products. The results suggested that there were no detectable citrinin in 4 of the 11 samples, however citrinin with the levels between 0.10-594 ng/kg has been detected in the other 7 samples. It indicates that the proposed method can also be applied to carry out the quantitative detection of citrinin for other Monascus -fermented products.